2020
DOI: 10.1155/2020/5694670
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplant Donor-Specific Anti-HLA Antibodies and the Risk for Rejection-Related Graft Failure of Kidney Allografts

Abstract: Background. The presence of donor-specific antibodies (DSAs) against HLA before kidney transplantation has been variably associated with decreased long-term graft survival. Data on the relation of pretransplant DSA with rejection and cause of graft failure in recipients of donor kidneys are scarce. Methods. Patients transplanted between 1995 and 2005 were included and followed until 2016. Donor-specific antibodies before transplantation were determined retrospectively. For cause, renal transplant biopsies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 31 publications
2
17
3
Order By: Relevance
“…While the majority of acute T cell mediated rejections occur within the first 3-6 months after transplantation, the incidence declines to virtually zero by 3-5 years post kidney transplantation (KT) (1). This decreased risk is thought to arise from a gradual decrease in alloreactivity of T-cells to donor antigen while response to alloantigen of a third party is retained.…”
Section: Introductionmentioning
confidence: 99%
“…While the majority of acute T cell mediated rejections occur within the first 3-6 months after transplantation, the incidence declines to virtually zero by 3-5 years post kidney transplantation (KT) (1). This decreased risk is thought to arise from a gradual decrease in alloreactivity of T-cells to donor antigen while response to alloantigen of a third party is retained.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, re-transplantation, grafts from deceased donor and high level of panel reactive antibody (PRA) have been reportedly associated with increased risk of graft loss and rejection after transplantation [11,12]. In current cohort, these risk factors were also evaluated and none of them demonstrated signi cant relevance with rejection in multivariate analysis.…”
Section: Discussionmentioning
confidence: 93%
“…The patients who received desensitization with plasmapheresis and low-dose intravenous immunoglobulin before kidney transplantation experienced successful transplantation. Betjes et al (5) confirmed that the presence of DSA against HLA before kidney transplantation was a risk factor for early graft rejection (mostly AMR). The above results have led nephrologists to believe that highly sensitized patients would increase the chances of successful kidney transplantation.…”
Section: Positive Panel-reactive Antibody With Delayed Graft Functionmentioning
confidence: 95%
“…DGF and AR post-transplantation usually appear in highly sensitized patients with positive PRA or positive crossmatch (5,19,20). We had two patients whose hyperacute rejection was related to positive PRA and needed to come back to use hemodialysis after transplanted nephrectomy ( Figure 2).…”
Section: Positive Panel-reactive Antibody With Delayed Graft Functionmentioning
confidence: 99%
See 1 more Smart Citation